All-fiber single-longitudinal-mode narrow linewidth fiber ring laser with cylindrical vector beam output. (4th October 2018) - Yao, Shuzhi; Yang, Yuguang; Shen, Ya; Han, Wenguo; Jiang, Youchao; Jian, Shuisheng
Abstract: A single-longitudinal-mode (SLM) fiber ring laser with cylindrical vector beam (CVB) output is experimentally demonstrated. Mode selection and spectrum filtering are achieved by introducing a two-mode fiber Bragg grating (TM-FBG) as an output mirror simultaneously. The SLM operation is obtained by using a compound ring cavity laser structure together with an un-pumped EDF acting as a saturable absorber. The fiber laser operates at a single wavelength of 1545.99 nm with a 20 dB linewidth of about 7.1 kHz and an optical signal to noise ratio of more than 68 dB. Through adjusting the intra-cavity polarization controllers, stable narrow linewidth radially and azimuthally polarized CVBs are both obtained.